Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
f(3)=0, f(4)=-60
f(n) = f(n-1) + (-60)
Step-by-step explanation:
Arithmetic Sequences
The arithmetic sequences are identified because any term n is obtained by adding or subtracting a fixed number to the previous term. That number is called the common difference.
The equation to calculate the nth term of an arithmetic sequence is:
f(n)=f(1)+(n-1)r
Where
f(n) = nth term
f(1) = first term
r = common difference
n = number of the term
The given sequence has two known terms: 120, 60, ...
The common difference is found by subtracting consecutive terms:
r = 60 - 120 = -60
Thus the next two terms are:
f(3)=120+(3-1)(-60)=120-120 = 0
f(4)=120+(4-1)(-60)=120-180 = -60
Since each term is calculated as the previous term plus -60, then the recursive formula is:
f(n) = f(n-1) + (-60)
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.